Świat, w którym „kariera robi karierę” – o satysfakcji z kariery i poczuciu zawodowego sukcesu - Cybal-Michalska, Agnieszka (Wydawnictwo Naukowe UAM, 2013)
Multi-contextual social changes imply definitely new ways of their interpretation and they order reflections about the predicament of the contemporary human being, including his or her being managers of their careers. Society has become an area where individuals can show their initiative. A contemporary study of career demands an inclusion of multi-contextual changes in the job world, changes that present employees with new requirements. The most important ones are the increase of the role attributed to a career and the ability to plan, manage and monitor one’s own career in a lifelong perspective. Considerations of a career cannot disregard the issue of the subjective sense that individuals find in their own careers in the context of possibilities that a man can have a satisfactory career.
The world in which “career makes a career” – about career satisfaction and a sense of professional success
Keywords: career; career planning; career monitoring; successful career; subjective sense of; satisfactory career